Law and Person: Modernity and Forecasting - Onishchenko, Nataliya M.; Lutskyi, Roman P. (International Journal of Criminology and Sociology, 2022)
This study will investigate the efficiency of law, considering the relevant objective and subjective factors. The authors would like to emphasise that in no case this publication is intended to cast doubts on the universality of legal provisions, but rather, on the contrary, to emphasise it; as well as to emphasise what modern law must demonstrate nowadays, so that no such doubts arise in relation to this paper. The law itself is not effective – it is free people, who are subjects of law in their relations. A free person is an intelligent being who has the will, the gift of thinking, is capable of producing tools and can consciously use them. However, the mere biological in human does not define it as a person. Personality is described by a combination of biological content and social qualities. That is why the latter acts as a legal subject that embodies the legal existence, the principle of law, and acts as its carrier and implementer. An important issue in this context is the clear delineation of concepts such as progress, progressive change, and the usual (appropriate) standardisation, the proper performance of a certain phenomenon of its mandatory functions. In this study, the authors will try to answer the extent to which the law demonstrates its relevance in the life of the average person, civil society, the state to address certain contemporary issues.